2014
DOI: 10.1038/nature13448
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing of normal cells reveals developmental lineages and mutational processes

Abstract: The somatic mutations present in the genome of a cell have been accumulated over the lifetime of a multicellular organism. These mutations can provide insights into the developmental lineage tree 1 , the number of divisions each cell has undergone and the mutational processes that have been operative 2 . Here, we conducted whole genome sequencing of clonal lines 3 derived from multiple tissues of healthy mice. Using somatic base substitutions, we reconstructed the early cell divisions of each animal demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
270
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 334 publications
(292 citation statements)
references
References 29 publications
21
270
1
Order By: Relevance
“…Given the inherent mutagenicity of 5ClC described here, when a cell having this lesion burden replicates, it would acquire about 3.3-99 new mutations. This number represents a notable increase over the spontaneous mutation rate, estimated for mammalian cells to be on average 1.1-1.5 mutations per cell division (52,53). Given that no repair pathway specific for 5ClC has yet been described (perhaps explaining the accumulation and persistence of this lesion in the genome), it is plausible that 5ClC is an important contributor to the mutagenic burden previously observed in tissues subjected to chronic inflammation (54,55) and thus increases the probability that such tissues progress toward malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Given the inherent mutagenicity of 5ClC described here, when a cell having this lesion burden replicates, it would acquire about 3.3-99 new mutations. This number represents a notable increase over the spontaneous mutation rate, estimated for mammalian cells to be on average 1.1-1.5 mutations per cell division (52,53). Given that no repair pathway specific for 5ClC has yet been described (perhaps explaining the accumulation and persistence of this lesion in the genome), it is plausible that 5ClC is an important contributor to the mutagenic burden previously observed in tissues subjected to chronic inflammation (54,55) and thus increases the probability that such tissues progress toward malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Such factors include the number of available samples, the number of somatic mutations in a sample, the number of mutations contributed by different mutational signatures, the similarity between the patterns of the signatures of mutational processes operative in cancer samples, as well as the computational limitations of our framework. Nevertheless, in the past three years, our framework has proven robust and has described multiple similar and validated signatures across the spectrum of human cancer [3][4][5][15][16][17][18][19][20][21][22] .…”
Section: Factors Influencing Signature Extractionmentioning
confidence: 99%
“…This may be a reasonable assumption, although somatic mutations have been demonstrated in genome-wide surveys and are known to accumulate with age in mammals [328][329][330], but it is unclear how much they may contribute to normal phenotypic variation. For plants, where ample opportunity for somatic mutation exists and extensive research on genetic mosaicism has been conducted, Herrera [262] reviewed the available evidence and concluded that such genetic variation is only rarely responsible for appreciable portion of within-individual variation.…”
Section: The Central Argument: Fluctuating Asymmetry As a Measure Of mentioning
confidence: 99%